Kelayakan Usaha Salad Buah pada UMKM Kuliner Sehat: Tinjauan Aspek Pasar, Teknis, Manajemen, dan Keuangan - Mohammad Afrizal Miradji; Bayuadi Bayuadi; Miftachul Masrofin Fifmansyah; Anggi Maharani; Fitri Novita Putri Kirana; Rayhan Kanza Albani; Ella Djamila Syah (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to analyze the feasibility of a fruit salad business as a healthy culinary product developed by micro, small, and medium enterprises. The analysis focuses on market, technical, management, and financial aspects to provide a comprehensive evaluation of business viability. The research applies a descriptive approach using mixed methods by combining literature review, market observation, and simple quantitative analysis based on standard assumptions in the snack food industry. The results indicate that the fruit salad business has strong market potential driven by increasing consumer awareness of healthy lifestyles and changing consumption patterns. From a technical perspective, the production process is relatively simple, requires minimal equipment, and can be operated efficiently at a micro-scale level. Management analysis shows that a simple organizational structure is sufficient to support daily operations. Financial evaluation reveals that the business generates attractive profits, supported by low break-even levels, a short payback period, and a positive net present value. Overall, the findings confirm that the fruit salad business is economically feasible and operationally sustainable, making it a promising opportunity for healthy culinary-based MSMEs.